2020
DOI: 10.1186/s10194-020-1085-x
|View full text |Cite
|
Sign up to set email alerts
|

Different doses of galcanezumab versus placebo in patients with migraine and cluster headache: a meta-analysis of randomized controlled trials

Abstract: Background: Galcanezumab is a novel monoclonal antibody that target to calcitonin gene-related peptide (CGRP). It has been tested for the preventive treatment of migraine and episodic cluster headache by multiple randomized clinical trials (RCTs) and have been found to reduce headache frequency. Methods:We systematically searched PubMed and Embase on Cochrane Central Register of Controlled Trials (CENTRAL) from the earliest date to August 1, 2019. Relative risk (RR) and weighted mean difference (WMD) were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
1
14
0
1
Order By: Relevance
“…The monoclonal antibodies against calcitonin gene-related peptide (CGRP) or its receptor including eptinezumab, fremanezumab, galcanezumab, and erenumab are explicitly developed for the prevention of migraine. Existing research confirmed that the galcanezumab are one of the most effective and safe for migraine prevention (12,13). Moreover, erenumab and eptinezumab were also proved to be safe and effective in preventing episodic and chronic migraines (14)(15)(16).…”
Section: Introductionmentioning
confidence: 91%
“…The monoclonal antibodies against calcitonin gene-related peptide (CGRP) or its receptor including eptinezumab, fremanezumab, galcanezumab, and erenumab are explicitly developed for the prevention of migraine. Existing research confirmed that the galcanezumab are one of the most effective and safe for migraine prevention (12,13). Moreover, erenumab and eptinezumab were also proved to be safe and effective in preventing episodic and chronic migraines (14)(15)(16).…”
Section: Introductionmentioning
confidence: 91%
“…After the analysis of our data, we found few limitations in our study which cannot be avoided through existing researches. First, numerous previous studies have concluded evidence to use other CGRP monoclonal antibodies such as ubrogepant, galcanezumab and rimegepant, for the treatment of migraine [20][21][22]. However, as interventions in our study were related to different dosage regimens of eptinezumab and placebo, we can only conclude the advantages of eptinezumab compared with placebo.…”
Section: Discussionmentioning
confidence: 62%
“…Our study has several strengths. The large number of included trials is the main strength of our study when compared to previous meta-analysis studies [25][26][27]. We only included randomized placebo-controlled clinical trials to ensure high-quality evidence.…”
Section: Discussionmentioning
confidence: 99%